Design and Assessment of Pastes for the Reattachment of Fractured Porous Stones - Maria Apostolopoulou; Evangelia Ksinopoulou; Eleni Aggelakopoulou; Anthi Tsimereki; Asterios Bakolas; Pagona-Noni Maravelaki (Heritage)
Ancient stone masonry is a composite structure, mainly comprised of stone elements. During restoration, stone elements are sometimes found to present serious fragmentation, and their structural continuity must be re-established. In such cases, an adhesive material can be applied to reattach the detached fragment to its original position, with or without the use of pins or anchors, according to the size of the fragment and its position. However, many considerations must be taken into account regarding compatibility with the ancient material and the performance and longevity of the intervention. In the current study, a series of pastes are designed for the reattachment of stone fragments, with and without the concurrent use of titanium pins, aiming to re-establish the continuity of the porous stone elements of the Acropolis circuit wall. The designed pastes are examined in terms of physical and mechanical characteristics and assessed in relation to their compatibility with the original stone material, while their effectiveness as adhesive and/or anchoring materials is evaluated through a real-time and -scale pilot application on site at the Acropolis monument work site using fragments of the original ancient stone material. The natural lime–metakaolin paste presents the optimum results as an adhesive and anchoring material.